Urban Area Revitalisation Programme Implementation Conditions in the Province of Warmia and Mazury - Farelnik, Eliza (Olsztyn Economic Journal, 2012)
This paper identifies the major factors that are the conditions for implementation of local urban area revitalisation programmes. Studies conducted in selected towns of the province of Warmia and Mazury showed that the availability of own and external funding for project implementation, accumulation of social problems in the areas subject to revitalisation, the size and diversity of entities involved in the revitalisation process and the lack of comprehensive legal regulations concerning revitalisation process organisation (absence of the Act on Revitalisation) were the most important factors influencing the revitalisation processes among those implementing and coordinating the programmes.